Pembuatan Pestisida Nabati Dengan Cara Ekstraksi Daun Pepaya Dan Belimbing Wuluh - Rani Ariyanti; Elvi Yenie; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The use of botanical pesticides is one alternative that is safe and environmentally friendly to take advantage of the potential of plant extracts as pesticides to control pests. The purpose of this research is to study the effect of time variations of submersion to yield and pH. Test secondarymetabolites component of maximum yield and to test the toxicity of the extract obtained from test animals and estimating the LC₅₀ extract of Papaya leaf and starfruit in each submersion can kill mosquito larvae in 24 hours. The research was done by extraction method,and separation of secondary metabolites with rotary evaporator with a variation of submersion that is 1, 3, 5, 7 and 9 days, the ratio of material and solvent is 1:4. The highest result is pointed at 9 days submersion, 9,9% and ph 5,73. Secondary metabolites components successfully tasted are alkaloids, flavonoids, tannins, saponins, and sulfur. LC₅₀ value of each pobit test is 2425,013 ppm obtained at 1 days of submersion, in 3, 5, 7 days showed LC₅₀ ppm consist of 2063,153 ppm, 1497,171 ppm, 1088,765 ppm. In 9 days has not result of LC₅₀ because the animals (object) have very high mortality.Keywords : Axtraction, botanical pesticides, LC5₅₀, papaya leaf, starfruit.